Exergy analysis study a Jander combined (gas-steam) power plant - مظلوم وسيم; محمد علي (Latakia University Journal -Engineering Sciences Series, 2024)
In this research an analysis of exergy was carried out in a combined (gas-steam) Gander thermal power plant to generate electrical energy at several variable loads ,modeling was done on the EES program (Engineering Equation Solver) ,where the actual data of the power plant’s work was entered ,and the rest of the parameters were calculated based on EES ,and the mathematical equations necessary for the exergy analysis of the parts of the thermal cycle were programmed by adopting on exergy equilibrium equations in each component of the power plant , Determining the exergy losses and exergy efficiency in each component ,the exergy was analyzed at variable loads (75%,100%) for each of the air compressor ,combustion chamber ,gas turbine ,(HRSG) heat recovery steam generator ,steam turbine and air cooled condenser. The effect of several investment factors on the oxygen efficiencies at the station was also studied: ambient temperature ,condenser pressure.